Compensation of intra-channel nonlinear fibre impairments using simplified digital back-propagation algorithm - Rafique, Danish; Mussolin, Marco; Forzati, Marco; Mårtensson, Jonas; Chugtai, Mohsan N.; Ellis, Andrew D. (Optics express, 2011)
We investigate a digital back-propagation simplification method to enable computationally-efficient digital nonlinearity compensation for a coherently-detected 112 Gb/s polarization multiplexed quadrature phase shifted keying transmission over a 1,600 km link (20 x 80 km) with no inline compensation. Through numerical simulation, we report up to 80% reduction in required back-propagation steps to perform nonlinear compensation, in comparison to the standard back-propagation algorithm. This method takes into account the correlation between adjacent symbols at a given instant using a weighted-average approach, and optimization of the position of nonlinear compensator stage to enable practical digital back-propagation.